Multifunctional Carbon Foam with Nanoscale Chiral Magnetic Heterostructures for Broadband Microwave Absorption in Low Frequency - Hao Zhang; Kaili Kuang; Yifeng Zhang; Chen Sun; Tingkang Yuan; Ruilin Yin; Zeng Fan; Renchao Che; Lujun Pan (Nano-Micro Letters)
Highlights A novel multifunctional carbon foam with nanoscale chiral magnetic heterostructures is constructed, in which the interconnection network provides strong conduction loss. The interfacial polarization loss induced by the FeNi-carbon interfaces is confirmed by the density functional theory calculations, and the magnetic pinning and coupling effects are revealed by the micromagnetic simulation. The composite foam exhibits an ultrabroad effective absorption bandwidth (EAB) of 14 GHz and a C-band EAB of 4 GHz, achieving the full C-band coverage.